Gold nanoparticles to enhance ophthalmic imaging. (15th October 2020) - Chen, Fang; Si, Peng; de la Zerda, Adam; Jokerst, Jesse V.; Myung, David
Abstract : Gold nanoparticles are promising OCT and PAI contrast agents for ophthalmic imaging because of their high light scattering/absorption from SPR. Abstract : The use of gold nanoparticles as diagnostic tools is burgeoning, especially in the cancer community with a focus on theranostic applications to both cancer diagnosis and treatment. Gold nanoparticles have also demonstrated great potential for use in diagnostic and therapeutic approaches in ophthalmology. Although many ophthalmic imaging modalities are available, there is still a considerable unmet need, in particular for ophthalmic molecular imaging for the early detection of eye disease before morphological changes are more grossly visible. An understanding of how gold nanoparticles are leveraged in other fields could inform new ways they could be utilized in ophthalmology. In this paper, we review current ophthalmic imaging techniques and then identify optical coherence tomography (OCT) and photoacoustic imaging (PAI) as the most promising technologies amenable to the use of gold nanoparticles for molecular imaging. Within this context, the development of gold nanoparticles as OCT and PAI contrast agents are reviewed, with the most recent developments described in detail.